Surfing the World of Knowledge: Analytical Case Studies of Digital Liberties in the United States - Liu, Dr Yan Quan (Independently published, 2021)
This work compiles a database that provides analytical case studies of typical digital libraries as an enhancement for educating and learning to meet the needs of students, librarians, scholars, and those who are interested in this resource.
Keywords: dept.ils